Optimal distribution process for semiconductor manufacturer - Goh, Tian Meng. (2008)
Semiconductor manufacturing is one of the most capital-intensive industries in the world. The industry is characterized by rapid advances in technology, short product life cycles, relentless downward cost pressure, ever increasing quality goals and frequent fluctuation in supply & demand. In such an industry, the only constant is change and the pressure for cost reduction is relentless. Resent trends for the cost pressure had been stretched to the logistics cost of the industry. Logistics process is the physical link between the company and its customers. It is one of the critical success factors of the company This dissertation aims to analyze and optimize the logistics cost of a semiconductor manufacturer. All critical components, which form the overall logistics costs are studied in depth. These components namely inventory holding, warehousing and transportation are subsequently translated into mathematical logic and developed into spreadsheet modules that forms the logistics cost model. The logistics cost model can be use to simulate logistics operation and subsequently derive an optimal logistics model for the company. An existing logistics operation is sited as the base scenario in which the various cost components were computed using the logistics cost model. Sensitivity test is conducted using the cost model to evaluate the impact of the various components.